Analisis tingkat motivasi belajar dan berlatih pada atlet-pelajar PPLOP Jawa Tengah tahun 2020 - Agam Akhmad Syaukani; Nur Subekti; Muhad Fatoni (Jurnal Keolahragaan, 2020)
Pemerintah daerah melalui dinas pemuda dan olahraga memiliki program pemusatan latihan bagi atlet pelajar setingkat SMA yang bertajuk Pusat Pendidikan dan Latihan Olahraga Pelajar (PPLOP). Efektivitas program PPLOP sangat bergantung dari prestasi atlet di lapangan dan di bangku sekolah. Penelitian ini bertujuan untuk mengetahui tingkat motivasi atlet-pelajar PPLOPD Jawa Tengah dalam berlatih  dan belajar di sekolah. Penelitian ini melibatkan 36 atlet dari cabang olahraga beregu. Metode survey deskriptif kuantitatif presentase digunakan untuk menjabarkan tingkat motivasi latihan (ML) dan motivasi belajar (MB). Uji beda juga dilakukan untuk mengetahui perbedaan tingkat ML dan MB antara pemain inti dan pemain cadangan pada sampel yang dilibatkan. Hasilnya sebanyak 47% atlet memiliki tingkat MB yang tinggi, 39% dalam tingkat sedang, dan 14% tergolong memiliki tingkat MB rendah. Tingkat ML dalam kategori tinggi 11,5%, kategori sedang 77%, dan kategori rendah 11,5%. Dalam uji beda yang dilakukan diketahui tidak ada perbedaan yang signifikan antara tingkat ML dan MB (p0,05) pada pemain inti dan pemain cadangan. Analysis of Level of Learning and Training Motivation among Student-athletes in Central Java PPLOP 2020 AbstractThe government through Deputy of Youth and Sport has a training center program for highschool student namely Student’s Center for Education and Training (PPLOP).The program effectivity depends on the student’s performance on (in training) and off the court (in education). This study aims to collect information on student motivation toward training and learning. There are 36 participants in this study. All came from team sports athletes.Descriptive quantitative percentage was used as research method which using motivation questionnaire to collect data from the participants for both training motivation (ML) and learning motivation (MB).T-test was also conducted to study the variant difference on motivation between starter and subtitutes player. The results came as follow, on MB there are  47% of the participants were categorized as highly motivated, 39% moderately motivated and only 14% categorized having low motivation. Meanwhile for ML, there are 11.5% of the participants are highly motivated, 77% are moderately motivated, and 11,5% showing low level of motivation. T-test conducted among starter and subtitutes player revealed that the difference on the level of ML and MB were not statistically significant (p0.05) among those subjects.